Pengetahuan, sikap, persepsi masyarakat dan tenaga kesehatan terhadap obat halal : Literature Review - Septiandani, Zunna; Latifah, Elmiawati; Yuliastuti, Fitriana (Universitas Muhammadiyah Magelang, 2023)
Abstract Indonesia is a country with a majority Muslim population, so the halal status of a product is very important in Indonesia. One indicator of halal products is medicine. Medicine itself is an important thing in the world of health. In a Muslim community, it is obligatory to know and pay attention to the drugs that will be consumed, besides that Health Workers are obliged to know about the halalness of the drugs that will be prescribed. Public awareness and knowledge related to the halalness of a drug in society, especially in Islam, is still a complex problem. This has an impact on the level of knowledge, attitudes, and perceptions of the public and health workers regarding the unavailability of a drug consumed or prescribed. This research was conducted to know knowledge,attitudes, perceptions community and medics towards halal pharmaceutical. The search for data in this study used the Google Scholar database with the keywords